2017
DOI: 10.1177/1010428317695027
|View full text |Cite
|
Sign up to set email alerts
|

MTA3 regulates malignant progression of colorectal cancer through Wnt signaling pathway

Abstract: MTA3 overexpression has been implicated in carcinogenesis. The aim of the present study was to explore the clinical significance and biological roles of MTA3 in human colorectal cancer and colorectal cancer cells. A total of 80 cases of colorectal cancer tissues were examined by immunohistochemistry for MTA3 protein expression. We analyzed the relationship between MTA3 and clinical factors and the results showed that MTA3 was overexpressed in 51.25% (41/80) cancer cases. There was significant associations betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 23 publications
2
4
0
Order By: Relevance
“…Then, it was found that the emodin/MTA3 axis play a crucial role in regulating cardiac fibrosis. This is consistent with the recognized role of MTA3 in regulating a variety of cellular events ( Jiao et al., 2017 ). As a transcription factor, MTA3 becomes a cancer suppressor by inhibiting the proliferation, invasion, and migration of cancer cells ( Ma et al., 2016 ).…”
Section: Targets and Studies Of Emodin Against Anti-cardiovascular DIsupporting
confidence: 91%
“…Then, it was found that the emodin/MTA3 axis play a crucial role in regulating cardiac fibrosis. This is consistent with the recognized role of MTA3 in regulating a variety of cellular events ( Jiao et al., 2017 ). As a transcription factor, MTA3 becomes a cancer suppressor by inhibiting the proliferation, invasion, and migration of cancer cells ( Ma et al., 2016 ).…”
Section: Targets and Studies Of Emodin Against Anti-cardiovascular DIsupporting
confidence: 91%
“…The study suggests an abnormally high expression of MTA2 in CRC tissue and MTA2 is associated with prognosis CRC (25). Additionally, Jiao et al have revealed MTA3 overexpression contributes to cell proliferation, invasion, migration, and cell cycle progression of CRC cells (26). Combined with our findings that ZNF217 knockdown could significantly reduce the expressions of MTA2 and MTA3, we inferred that ZNF217 might contribute to CRC carcinogenesis and development by combining its zinc finger domain to the NuRD complex region of MTA2/MTA3.…”
Section: Effects Of Znf217 Knockdown On Mta2 Mta3 Snai1 and E-cadherin Proteins Expression Levelssupporting
confidence: 83%
“…28 Study has found that MTA3 can regulate malignant progression of human cancer through various signaling pathways. 29 -31 Here, we reported that DDX5 knockdown inhibited migration and invasion of BCC cells. However, we will further investigate the expression of DDX5 in the more aggressive BCC subtypes based on their morphologies in our future work.…”
Section: Discussionmentioning
confidence: 89%